A Jungian Psychological Study of Nora Seed’s Introverted Personality in The Midnight Library: A Literary Analysis - Siregar, Namira Az Zahra; Zawawi, Moh (Journal of Language and Literature Studies, 2025)
The phenomenon of introverted personality represents a significant area of inquiry in both psychology and literary studies, as it captures the complexity of individuals characterized by introspection and emotional sensitivity. In Matt Haig’s The Midnight Library, the protagonist Nora Seed embodies introverted tendencies through her inner conflicts and existential pursuit of meaning. This study aims to examine the representation of Nora Seed’s introverted personality by employing Carl Gustav Jung’s psychological typology, with a specific focus on the four primary functions: thinking, feeling, sensing, and intuition. Jung’s framework is employed in this analysis because it offers a comprehensive theoretical lens for understanding the internal dynamics of literary characters, in contrast to other psychological approaches that predominantly emphasize observable behavior. Methodologically, this research adopts a qualitative descriptive-analytical design, involving close reading, systematic note-taking, and thematic coding of relevant textual evidence from the novel. The findings demonstrate that Nora exhibits all four introverted functions: a proclivity for logical reflection prior to action (thinking), the deep and nuanced processing of emotions (feeling), heightened attentiveness to sensory detail (sensing), and the interpretation of lived experiences through symbolic and abstract possibilities (intuition). The study concludes that Nora Seed represents the individuation process of an introverted subject, a portrayal that not only advances psychological literary criticism but also contributes to broader scholarly discourse on mental health and self-acceptance within contemporary society.